ANALISA CYBERCRIME PENCURIAN DATA PRIBADI MODUS APLIKASI PINJAMAN ONLINE DAN DIGITAL BANKING - Sugiarto, Evan; Oscar, Vincentius; Simanungkalit, Dewi Sartika (Legal Standing : Jurnal Ilmu Hukum, 2024)
These technological advances have resulted in tremendous efficiency for the economy. Financial institutions have changed approaches and practices. His financial business. However, rapid technological progress has resulted in negative consequences, such as an increase in more sophisticated cyber crimes. This research aims to examine technology-based crimes involving data theft using online lending and digital banking modes. This research uses a normative juridical type with data collection using literature studies, as well as correlative analysis. The results of this research show that criminals collaborate with financial service institutions. Using sophisticated information technology and computers to steal client online loan application data. Financial service institutions usually only commit document falsification, embezzlement and corruption as victims. Efforts to prevent these crimes include the ITE Law which regulates formal cyber crimes.